Water conservation strategies for Beijing Capital Region. - Jenny, Hubert (ADB briefs., 2019)
Beijing is the second largest city in the world, but it also ranks as one of the most water stressed cities. Faced with limited options, Beijing can only sustainably meet the additional water demand by 2030 through enhanced water conservation. The brief describes the current situation in the capital of the People Republic of China and the proposed way forward for water conservation, including principles for groundwater recharge, wastewater reuse, carbon storage, and water tariff rebates.